2001
DOI: 10.1083/jcb.153.4.865
|View full text |Cite
|
Sign up to set email alerts
|

Essential Roles of Drosophila Inner Centromere Protein (Incenp) and Aurora B in Histone H3 Phosphorylation, Metaphase Chromosome Alignment, Kinetochore Disjunction, and Chromosome Segregation

Abstract: We have performed a biochemical and double-stranded RNA-mediated interference (RNAi) analysis of the role of two chromosomal passenger proteins, inner centromere protein (INCENP) and aurora B kinase, in cultured cells of Drosophila melanogaster. INCENP and aurora B function is tightly interlinked. The two proteins bind to each other in vitro, and DmINCENP is required for DmAurora B to localize properly in mitosis and function as a histone H3 kinase. DmAurora B is required for DmINCENP accumulation at centromer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
429
1
9

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 441 publications
(475 citation statements)
references
References 36 publications
36
429
1
9
Order By: Relevance
“…The behavior of chromosomes in the DdINCENP null cells contrasted sharply with that of wild-type cells, which always displayed normal segregation of chromosomes (Graf et al, 2003; Figure 4; see Video 5). The mitotic and the cytokinetic defects displayed by the DdINCENP null cells were consistent with the observation in other organisms that INCENP plays important roles during mitosis (Kaitna et al, 2000;Adams et al, 2001b).…”
Section: Ddincenp Is Important For Mitosissupporting
confidence: 73%
See 1 more Smart Citation
“…The behavior of chromosomes in the DdINCENP null cells contrasted sharply with that of wild-type cells, which always displayed normal segregation of chromosomes (Graf et al, 2003; Figure 4; see Video 5). The mitotic and the cytokinetic defects displayed by the DdINCENP null cells were consistent with the observation in other organisms that INCENP plays important roles during mitosis (Kaitna et al, 2000;Adams et al, 2001b).…”
Section: Ddincenp Is Important For Mitosissupporting
confidence: 73%
“…It can stimulate the kinase activity of Aurora B and is also a substrate of Aurora B kinase (Kang et al, 2001;Honda et al, 2003). In both Drosophila and Caenorhabditis elegans, depletion of INCENP by RNAi causes failed chromosome congression at metaphase, mislocalization of Aurora B, and cytokinesis defects (Kaitna et al, 2000;Adams et al, 2001b). Also, in Xenopus mitotic egg extracts, immu-nodepletion of INCENP induced the formation of monopolar spindles (Sampath et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It inhibits apoptosis (Altieri, 2001) and is involved in the spindle checkpoint and the regulation of proper chromosomal segregation during mitosis by acting as a member of the chromosomal passenger protein family (Li et al, 1998;Adams et al, 2001). A number of studies have demonstrated that the suppression of survivin results in cells with multipolar mitotic spindles that are either multinucleated or aneuploid (Li et al, 1999;Beltrami et al, 2004;Kappler et al, 2004).…”
mentioning
confidence: 99%
“…[8]). They are involved in some checkpoint regulation pathways including spindle assembly checkpoint, alignment of metaphase chromosomes, chromosomal biorientation, kinetochore-microtubule association and cytokinesis [9]. Aberrant expression of Aurora kinases may disturb checkpoint functions particularly in mitosis and this may lead to deregulation of cell division and trigger the development of tumours [10,11].…”
Section: Aurora Kinases and Cancermentioning
confidence: 99%